Internship satisfaction : a preliminary study on undergraduates from the Faculty of Business and Finance of Universiti Tunku Abdul Rahman - Heng, Kawai; Ch’ng, Phui Jean; Hung, Wen Rong; Ooi, Xui Chi; Soh, Chien Yin (2011)
Internships have been gradually increasing in terms of its incorporation into the academic curriculum of tertiary education providers and have been made compulsory as a requirement for graduation in some parts of the world, including Malaysia. Despite its increasing presence and importance, little research has been done on internship satisfaction whereby it has been one area of research that has been largely neglected. The aim of this study is to identify the factors which may contribute to internship satisfaction among business undergraduates. There were five core factors identified through the literature as predictors of internship satisfaction namely individual factors, university support, job characteristics, organizational environment, and contextual factors. To explore further, a quantitative research involving 310 business undergraduates who had undergone internship from the Faculty of Business and Finance of Universiti Tunku Abdul Rahman (UTAR) was conducted. The relationship among variables were evaluated and analyzed with Pearson Correlation analysis, independent samples ttest, and multiple regression analysis. Results showed that four out of five factors were good predictors of internship satisfaction (individual factors, university support, job characteristics, and organizational environment) with organizational environment as having the most significant influence on internship satisfaction. This study may provide pointers for the university faculty for a more effective conduct of internship being its first time in implementation, assist employers in their attracting, recruiting, and retaining effort by being aware of undergraduates’ expectations of satisfaction and most importantly, helping undergraduates to get the most from their internship and to have a more satisfying internship experience.